Comparison on taste threshold between adult male white cigarette and clove cigarette smokers using Murphy clinical test method - Tapilatu, Ronald Reyses; Haroen, Edeh Rolleta; Wihardja, Rosiliwati (Padjadjaran Journal of Dentistry, 2008)
The habit of smoking white cigarettes and clove cigarettes may affect the gustatory function, that is, it will cause damage to taste buds, resulting in an increase in gustatory threshold. This research used the descriptive comparative method and had the purpose of obtaining an illustration of gustatory threshold and compare gustatory threshold in white cigarette smokers and clove cigarette smokers in young, male adults. For gustatory threshold evaluation, the Murphy method was used to obtain a value for perception threshold and taste identification threshold using sucrose solution of 0.0006 M-0.06 M concentration. Research results indicate that the perception threshold and identification threshold of young, male adult smokers are 0.0119 M and 0.0292 M. Young, male adult clove cigarette smokers have a perception threshold and identification threshold of 0.0151 M and 0.0348 M. The conclusion of this research is that the perception threshold of young, male adult white cigarette smokers and clove cigarette smokers are the same, whereas the identification threshold of young, male adult white cigarette smokers and clove cigarette smokers are different, that is, the identification threshold of clove cigarette smokers is higher than that of white cigarette smokers.